PERANCANGAN SISTEM INFORMASI PELAPORAN KEGIATAN TEAM SAMPLING NESTLE BERBASIS WEB (Studi Kasus : Team Sampling Nestle Fixed Kitchen Jakarta 1 PT Iris Worldwide Indonesia) - Diah Rahmawati (2021)
The development of information technology can not be separated from the rapid development of computer technology, because the computer is a medium that can provide convenience for humans in completing a job. PT Iris Worldwide Indonesia, which is engaged in marketing promotion of PT Nestle Indonesia's products, is still conducting manual reporting of sampling activities conducted by the team. Based on this, the author will build a website-based information system to facilitate the work of the sampling team in terms of reporting. The method used by the author is the Waterfall Method with details and problem identification using the PIECES method, the programming language used is PHP and the database used is MySQL. The expected result is a web-based application of information systems for reporting Nestle sampling team activities.